A LOW-NOISE LOW-POWER SECOND-ORDER COMPENSATED CMOS BANDGAP REFERENCE - Sigit Yuwono; Arie van Staveren (TEKTRIKA, 2004)
The design of a low-noise and low-power second-order bandgap reference voltage source using a linear combination of two base-emitter voltages with only one scaling factor is treated. The design takes into account the temperature dependency of the resistors and the finite current gain of BJT’s. The circuit is integrated in a CMOS process. The output voltage is approximately 140 mV with an average temperature dependency of 22.5 ppm/K in the range of 0°C to 120°C. Its equivalent output noise voltage is 57.6nV/√Hz. The total current consumption is about 115 μA from a 2V voltage-supply.Keywords: bandgap reference, negative feedback, systematic design.